2015
DOI: 10.1021/mp500846u
|View full text |Cite
|
Sign up to set email alerts
|

Improved Biofilm Antimicrobial Activity of Polyethylene Glycol Conjugated Tobramycin Compared to Tobramycin inPseudomonas aeruginosaBiofilms

Abstract: The objective of this study was to develop a functionally enhanced antibiotic that would improve the therapeutic activity against bacterial biofilms. Tobramycin was chemically conjugated with polyethylene glycol (PEG) via site-specific conjugation to form PEGylated-tobramycin (Tob-PEG). The antibacterial efficacy of Tob-PEG, as compared to tobramycin, was assessed on the planktonic phase and biofilms phase of Pseudomonas aeruginosa. The minimum inhibitory concentration (MIC80) of Tob-PEG was higher (13.9 μmol/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 73 publications
3
43
0
Order By: Relevance
“…reported a 3.2‐fold increase in elimination of an established P. aeruginosa biofilm when treated with PEG‐conjugated tobramycin compared to the effect of a solution of the antibiotic. [ 38 ] Moreover, Suk et al. showed that low MW PEG‐coated nanoparticles moved through undiluted cystic fibrosis sputum up to 90‐fold faster than uncoated particles, but the penetration of identically coated larger nanoparticles were strongly hindered.…”
Section: Resultsmentioning
confidence: 99%
“…reported a 3.2‐fold increase in elimination of an established P. aeruginosa biofilm when treated with PEG‐conjugated tobramycin compared to the effect of a solution of the antibiotic. [ 38 ] Moreover, Suk et al. showed that low MW PEG‐coated nanoparticles moved through undiluted cystic fibrosis sputum up to 90‐fold faster than uncoated particles, but the penetration of identically coated larger nanoparticles were strongly hindered.…”
Section: Resultsmentioning
confidence: 99%
“…131 Furthermore, the relationship between charge-charge and hydrophobic interactions is not fully understood, and the chemical heterogeneity of biological gels lends the problem an additional layer of practical uncertainty. These difficulties notwithstanding, the cases of PEGylated tobramycin 132 and charge-reduced lysozyme 137140 suggest that engineering drugs with hydrogel interactions in mind can improve efficacy. Engineering drug interactions with biological gels may also lead to new functional biocompatible hydrogels, sidestepping the need for complex synthetic formulations.…”
Section: Discussionmentioning
confidence: 99%
“…However, the improvement in activity of the PEGylated tobramycin against biofilms was modest, because the PEG chain compromised the biological activity of the molecule. 132 One possible strategy to avoid reduced activity is to make the PEGylation reversible via hydrolysis, a strategy that has been investigated for gentamicin (another aminoglycoside) due to the potentially improved pharmacokinetic properties offered by PEGylation, but not studied in a biofilm context. 133 Reversible PEGylation may allow for gel penetration, as well as full activity of the hydrolyzed form.…”
Section: Interactive Filtersmentioning
confidence: 99%
“…To query the transport of the identified peptides in the CF sputum microenvironment, we conjugated synthetic peptides to carboxyl-modified polystyrene nanoparticles of 100 nm diameter and compared their mean squared displacement (MSD) in patient sputum with nanoparticles conjugated to mPEG 1 kDa. Recent studies have shown hydrophilic, net-neutral charge PEG polymer and polymer conjugates can improve transport of particles in CF sputum up to 90-fold compared to uncoated particles and improve therapeutic activity of antibiotics such as tobramycin against bacterial biofilms commonly associated with CF infections [17,[81][82][83].…”
Section: Discussionmentioning
confidence: 99%